(untitled) (Al-Mansour Journal, 2023)
Many mathematical techniques that can be utilized to quantify the leakage’s and drop outs of the students. Markov chains are considered the most applicable technique. In this paper, this phenomenon is investigated in the Nursing College –Baghdad University for the period between 2001 and 2004 by using Markov chain model.